PECULIARITIES OF THE PHENOMENON OF POLITICAL LEADERSHIP IN POST-SOVIET GEORGIA - Levan Nikoleishvili; Tamar Kiknadze (International Journal of Innovative Technologies in Social Science, 2020)
The socio-political processes developed in Georgia in the 90s of the twentieth century led to the political transformation of the country. The political changes that began during this period led to the ideological and value transformation of elite structures, including procedural changes in the mechanisms of elite circulation. All this was reflected in the country's domestic and foreign policy.In Georgian reality, the main part of the society is focused on a specific political figure, however, the elite groups united around this leader differ from each other in their values and ideological orientation. At the same time, all post-Soviet political leaders followed different paths of accumulating social and political capital, which became an important component of developing their individual political charisma.The article discusses the features of 4 political leaders of post-Soviet Georgia (Z. Gamsakhurdia, E. Shevardnadze, M. Saakashvili, B. Ivanishvili) and the political processes related to them.